Comparison of Beauty Standards and Body Images on Disney Princesses and Female Villains - Rachel Silalahi; Kunto Adi Wibowo; Ikhsan Fuady (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
As the role of mass media has increased, people have become more obsessed with the ideal portrayal of “ideal beauty and body”. With Disney Princess, the media’s perception of “ideal beauty and body” even spread to younger audiences. This study aims to analyze the comparison of beauty standards and body image between Disney Princesses and Female Villains. A quantitative content analysis method consists of two categories; videlicet Beauty Standards and Body Image are used to analyze the visualization of the characters. Six indicators for Beauty Standards and three for the Body Images category. This research found no differences in Beauty Standards and Body Images between Disney Princesses and Female Villains. Still, two indicators in Beauty Standards are declared significant, namely Hair Color and Physical Appearance. Eventually, this study declared no significant indicators difference between subjects; still, there are two indicators declared significant, which can lead to audiences’ misperception